Peculiarities of Young Long-term Unemployed Integration in to the Labour Market - Rudžinskienė, Rasa (Socialinė teorija, empirija, politika ir praktika, 2013)
SummaryThe theatrical features of young people unemployment and integration into the labour market have been analysed. The concepts of labour market, unemployed, young long-term unemployed have been identified. The main factors of young people integration into the labour market have also been examined. The quantitative and qualitative research of young unemployed and employers is presented in the article in order to characterise the most important features of young long-term unemployed as well as to create their social portrait. The research has been accomplished in order to represent the youth opinion of labour exchange services and their quality. This research has also helped to reveal the reasons for youth (long-term) unemployment in the employers’ and young people’s opinion.Key words: labour marker, young long-term unemployed, social portrait.